Diagnosis and treatment of neurogenic bladder secondary to aortic dissection: A 8‐year retrospective study at a single center. Issue 8 (24th August 2022) - Zhou, Zhonghan; Gao, Yi; Li, Xing; Wang, Xuesheng; Liao, Limin
Abstract: Purpose: To review the characteristics of the neurogenic lower urinary tract dysfunction (NLUTD) secondary to aortic dissection (AD), analyze the clinical features, and discuss the treatment options. Methods: Ten individuals complaining of lower urinary tract syndrome following AD were enrolled in this study. Clinical characteristics, urological and neurological symptoms/signs, imaging examination, and intervention were reviewed. Liao's comprehensive classification system was used to precisely assess the lower and upper urinary dysfunction. Results: The urinary symptoms can be varied, including dysuria, incontinence, and frequency. Individuals were divided into the detrusor overactivity (DO) and detrusor underactivity (DU) subgroups. Continence, impaired upper urinary tract functions (renal insufficiency, vesicoureteral reflux, upper urinary tract dilatation, and lower urinary tract functions (DO and/or detrusor external sphincter dyssynergia/detrusor bladder neck dyssynergia, DU, low bladder capacity, and compliance) were examined using video‐urodynamics. The principle of treatment is "low‐pressure bladder storage with complete bladder emptying, " and close follow‐up was recommended due to the volatile course of NLUTD. Conclusions: Both cardiovascular surgeons and urologists should pay attention to the occurrence of NLUTD following AD, and determine the most appropriate therapeutic option.